Nanostructured Multilayer Films Assembled from Poly(dopamine)‐Coated Carbon Nanotubes for Controlling Cell Behavior. Issue 5 (10th April 2017) - Li, Bo‐chao; Ren, Ke‐feng; Zhang, He; Jia, Fan; Wang, Jin‐lei; Chang, Hao; Wang, Yun‐bing; Ji, Jian
Abstract: Nano‐topographic surfaces have been used as an effective tool to control cell behavior such as adhesion and proliferation. In this study, multilayer films with nano‐topographic features were fabricated by alternatively assembling poly(l ‐lysine) (PLL) and poly(dopamine)‐coated carbon nanotubes (CNTs@PDA) layers. The growth of PLL/CNTs@PDA film presented a perfect linear relationship with the number of bilayers. A nanostructured morphology with interpenetrating CNT networks was observed by scanning electron microscopy (SEM). Adhesion and proliferation of endothelial cells (ECs) and smooth muscle cells (SMCs) on the PLL/CNTs@PDA multilayer films have been evaluated. The films support initial adhesion of both ECs and SMCs. Interestingly, the PLL/CNTs@PDA multilayer films were found to promote proliferation of SMCs and inhibited proliferation of ECs. Further, pheochromocytoma (PC12) cells were employed to evaluate the influence of PLL/CNTs@PDA multilayer films on the outgrowth of synapses. We found that the nanostructured surface significantly promoted the synapses of PC12 cell growth and formation. Our findings suggest that cytophilic surfaces with the nanostructured morphology have diverse effects on different cells, which sheds light on new design of biomaterial surfaces in cell‐based applications. Abstract : Caught on film : A multilayer film with nano‐topographic surface is fabricated through layer‐by‐layer assembly of poly(dopamine)‐coated carbon nanotubes (CNTs@PDA) and poly(l ‐lysine) (PLL). The adhesion and proliferation of endothelial cells, smooth muscle cells, and pheochromocytoma cells on the PLL/CNTs@PDA film were followed and compared.